Three-dimensional on-chip mode converter - Li, Ze-Zheng; Ouyang, Yang; Li, Zhong-Tian; Tian, Zhen-Nan; Zhang, Xu-Lin; Chen, Qi-Dai; Sun, Hong-Bo (Optics letters, 2023)
The implementation of transverse mode, polarization, frequency, and other degrees of freedom (d.o.f.s) of photons is an important way to improve the capability of photonic circuits. Here, a three-dimensional (3D) linear polarized (LP) LP mode converter was designed and fabricated using a femtosecond laser direct writing (FsLDW) technique. The converter included multi-mode waveguides, symmetric Y splitters, and phase delaying waveguides, which were constructed as different numbers and arrangements of circular cross section waveguides. Finally, the modes (LP and LP ) were generated on-chip with a relatively low insertion loss (IL). The mode converter lays a foundation for on-chip high-order mode generation and conversion between different modes, and will play a significant role in mode coding and decoding of 3D photonic circuits.